Pembrolizumab- and/or pazopanib-induced remitting seronegative symmetrical synovitis with pitting edema in a patient with renal cell carcinoma. (July 2020) - Bas, Onur; Ozbek, Aral; Guven, Denizcan; Aktepe, Oktay; Kılıc, Levent; Kertmen, Neyran; Erman, Mustafa
Introduction: Immune checkpoint inhibitors and angiogenesis inhibitors are novel treatment options for renal cell carcinoma and widely used in clinical practice. They are related with adverse events that occur as a consequence of immune system activation and inhibition of angiogenesis. Herein, we report a rare case of inflammatory arthritis seen in a patient treated with an anti Programmed cell death-1 pembrolizumab and an anti-vascular endothelial growth factor pazopanib. Case report: A 60-year-old Caucasian male presented to our clinic with inflammatory arthritis with pitting edema. He had been started on pembrolizumab therapy for metastatic renal cell carcinoma after enrolling in the KEYNOTE-679 study. After six cycles of treatment with pembrolizumab, metastasis had been determined in the lung. Then, the patient's therapy was changed to pazopanib. While the patient was on pazopanib treatment, he noticed a gradual swelling of both hands. Rheumatoid factor, anti-nuclear antibody and anti-cyclic citrullinated peptide were negative. Joint ultrasonography revealed acute tenosynovitis and soft tissue swelling with pitting edema, and a diagnosis of remitting seronegative symmetrical synovitis with pitting edema was made. Management and outcome: He was started on 10 mg prednisolone daily. His symptoms dramatically responded to corticosteroid. He continued to take pazopanib. Then, the patient was discharged with 10 mg prednisolone daily. Discussion: Pembrolizumab- and/or pazopanib-induced remitting seronegative symmetrical synovitis with pitting edema can be among the rare rheumatic immune-related adverse events that clinicians may encounter as the immune check point inhibitors and anti-VEGF use increases. Corticosteroid therapy can relieve symptoms and cessation of therapy may not be necessary.